A social ascension strengthened by the rhetorical construction of a family: the case of Quintus Aurelius Symmachus Eusebius (fourth century A.D.) - Pohlmann, Janira Feliciano (Dialogos, 2016)
Member of the Roman senate and the imperial power circle, the Neoplatonic Quintus Aurelius Symmachus Eusebius used his pen and his rhetoric’s knowledge for the preparation of documents which linked political theories and moral values to legitimize the actions and the need of a sovereign ruler. In this article we analyze some elaborations made by Symmachus especially in his Epistulae, Relationes and Orationes (I and II) in honor of Valentinian I.